Production model based on Lean Manufacturing and BPM to reduce the rate of returns in SMEs of garment printing - Carrasco Sayas, Jhoiser Luis (2023)
Small and medium-sized companies in the textile sector have deficiencies in the production area. It happened because they do not have a standardized process and adequate machine maintenance management. For this reason, analyzing the initial diagnosis of an SME company dedicated to textile printing presented problems in design and printing. Based on this, this research developed a proposed model to reduce the return rate, improve work areas' organization, and optimize delivery times. The production model is developed based on the Lean BPM (Business Process Management) and TPM (Total Productive Management) tools through a 5s continuous improvement approach. The improvement proposal is validated in the Arena 14 software, reducing the failure rate of the machines and the rate of returns from 7.95% to 5.97%